P198 Service evaluation of home spirometry following lung transplantation. (11th November 2022) - Chow, BHN; Iyer, K; Ridings, G; Webster, L; Clowes, H; Santhanakrishnan, K; Blaikley, J
Abstract : Introduction and Objectives: Following Lung Transplantation recipients perform regular spirometry to assess allograft function. Due to infection risks during the COVID pandemic, this was difficult to perform when vulnerable immunosuppressed patients were shielding. Therefore, we provided our patients with home spirometry allowing them to be perform spirometry remotely. Methods: Bluetooth spirobank spirometers and an app created by patientMpower to transmit the data were given to 164 lung transplant patients. The service was then evaluated by comparing results from the device against recent (>3 months) spirometry performed at the hospital. The views of clinicians and patients were also obtained about the service through questionnaires. Results: 164 patients were provided with home spirometers, 112 questionnaires were collected from clinicians following patient consultations and 94 patients were interviewed for their experience. Nearly a quarter of patients (23%) reported difficulties with the spirometer's initial setting up or using the smartphone app. The FEV1 and FVC readings from home spirometry correlated well with measurements taken in clinic with an R 2 of 0.69 and 0.59 respectively (p<0.01 n=78). Clinicians found home spirometry useful in 79.6% (n=112) of consultations and felt the need for hospital spirometry was removed in 63% of cases. Patients were asked to perform spirometry daily or once a week after lung transplantation depending on when they had their transplant. 50% of patients met this goal submitting readings at least three times per week. The median patient rating of the program was 9 out of 10 (10= excellent, n=91). Patient evaluations indicated that the spirometer was easy to use (91.4%), compact (86.0%), and the app was helpful (71.0%) (n=94). In comparison to the previous analogue spirometer, 88.4% of respondents preferred the new Bluetooth spirometer (n=73). Conclusion: We found Bluetooth home spirometer provided accurate results, which was useful in the clinical setting and is acceptable to patients. In addition, it provided real time remote monitoring aiding in assessment of allograft function, which was a benefit over the analogue counterpart particularly during COVID.